Policy on Development of S&T Information in the Current Digital Transformation Context - Huu Buong, Duong; Huy Thang, Vu; Tien Duc, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 39 No 2DO - 10.25073/2588-1116/vnupam.4439, 2023)
The article analyzes the role of science and technology (S&T) information and development policies, the relationship between information and policy, and a number of macro policies on S&T information. From that, the study proposes policies for the development of S&T information in the context of the current digital transformation.